Impact of physical exercise intervention and PPARγ genetic polymorphisms on cardio-metabolic parameters among a Chinese youth population. Issue 1 (1st April 2020) - Su, Juan; Wang, Hui; Tian, Yuanrui; Hu, Haixu; Gu, Wanjian; Zhang, Ting; Li, Mengxia; Shen, Chong; Gu, Harvest F
Abstract : Objective: Physical inactivity inChinese youth students particularly in senior high schools, who participate inthe National Higher Education Entrance Examination (NCEE) is very common. Inorder to explore the beneficial effects from physical exercise and education afterNCEE, we performed a P hysicalexercise I ntervention P rogram in the Y outh (PiPy) to evaluate the interaction with PPARγ genetic variants on cardiovascular and metabolicparameters. Methods: A total of 772 freshmen (males 610/females162) from high schools to university were recruited into the PiPy cohort, which was designedaccording to the National Student Health Standards in China. Anthropometric data were collected, whilephysical activities and body composition at the baseline of PiPy cohort weremeasured with SECAprotocols. Eighttagged single nucleotide polymorphisms (SNPs) in the PPAR γ gene were genotyped with TaqMan allelicdiscrimination. Results: After physical exercise intervention forthree months, in parallel with increased physical activities, BMI and skeletalmuscle content in all subjects was enhanced, while heart rate and bloodpressures were decreased. Furthermore, SNPs in 5'-UTR of the PPARγ gene, including rs2920502, rs9817428 and rs2972164, were found to be associated with the changes of BMI.Body weight in the subjects with BMI <18.5and 18.5-23.9 kg/m 2 were increased, while the obese subjects (BMI ≥24.0 kg/m 2 ) decreased. Conclusion: The present study for the first timedemonstrated that the PiPy could improve cardio-metabolic parameters such asheart rate, blood pressures and BMI for Chinese youth students after NCEE, inwhich the genetic interactive effects of PPAR γ should be included into obesityintervention.